Subcutaneous Administration of Monoclonal Antibodies in Oncology - Jackisch, C.; Müller, V.; Maintz, C.; Hell, S.; Ataseven, B. (Geburtshilfe und Frauenheilkunde, 2014)
Treatment with monoclonal antibodies (mabs) has become an established component of oncological therapy. The monoclonal antibodies available for this purpose are mainly administered intravenously in individually adapted doses according to body weight over longer treatment times. For other chronic diseases such as, for example, diabetes mellitus, the subcutaneous administration of drugs is an established therapy option. For the subcutaneous administration of larger volumes as needed for mab solutions the extracellular matrix of the subcutaneous tissue represents a problem. The co-formulation with recombinant human hyaluronidase makes the relatively pain-free administration of larger fluid volumes and thus the subcutaneous administration of monoclonal antibodies possible, as illustrated by the development of a subcutaneous formulation of trastuzumab. This constitutes a less invasive, time-optimised and flexible form of administration for patients with HER2-positive breast cancer that, with its fixed dosing possibilities, contributes to therapeutic safety. The example of trastuzumab shows that the subcutaneous administration of monoclonal antibodies can simplify oncological long-term therapy not only for the patients but also for the medical personnel.
Keywords: monoclonal antibodies; subcutaneous therapy; breast cancer; trastuzumab; oncology